Status embrionu. Perspektywa biomedyczna i etyczno-antropologiczna w świetle prac Papieskiej Akademii „Pro Vita" - Sikora, Adam (Poznańskie Studia Teologiczne, 2009)
The status of the human embryo is the subject of discussion in many environments. The way of perceiving many other bioethical issues depends on the solution to this problem. The Church also takes part in the discussion - in its official teaching as well as in more specialized sectors of its life. The works of Papal Academy „Pro Vita” constitute such a voice of the Church. It gathers scientists from such branches of science as philosophy, law and, first of all, medicine. In 2006 a session of the Academy took place and it was devoted to the status of the human embryo. The subject was formulated in two basic aspects: the biological status and the ethical status. The first one is about determining the biological structure of the embryo as an independent, unique structure typical for a human being. The second one is about determining its individuality, human distinction and dignity which demands protection and respect appropriate for a human being.